Study of heat Energy Disposal in Hollow Roof Cooling Water Tank - Sudirman Lubis; Farel H Napitupulu; Ilmi Abdullah; Tulus Burhanuddin Sitorus (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Cooling tank is defined as a heat exchanger whose working fluid material is water, and air which functions to cool water by direct contact with air which causes a small portion of the water to evaporate. This water will flow in the hollow roof which is expected to absorb heat as it passes through the cavity. This study aims to obtain the value of the effectiveness of the heat transfer rate on the hollow roof, as well as to determine the amount of energy in the cooling water tank of the hollow roof that can be discharged every hour and to determine the water flow required to supply the hollow roof. During the study, the results obtained varied with the volume of water entering about 0.00064 m³ in each cavity, with a pump capacity of 5.5 LPM. From the test data obtained, if the intensity of sunlight is low, the heat will be absorbed by the environment and vice versa if the intensity of sunlight is high, the heat will be absorbed by the water. That is why the intensity of sunlight greatly affects the data collection process. From the results obtained in the field at the time of the study for 7 days, the average water temperature was 28.4ºC. This result can be categorized as safe because the water temperature does not exceed or is not far from the temperature in the water tank with an average temperature of 40.5ºC.